Waste-to-Energy Technologies: Global Trends, Challenges, and Opportunities for Sustainable Development (Journal of Planner and Development, 2026)
The accumulation of municipal solid waste (MSW) has become an escalating environmental and public health concern, particularly in developing countries such as Iraq. Landfills are nearing their full capacity, while formal waste management systems are still in the process of development. At the same time, the growing demand for energy presents an additional challenge to sustainability efforts. This study is based on the hypothesis that Waste-to-Energy (WtE) technologies can offer a Partial solution to both the waste crisis and energy shortages. The primary objective of this research is to examine global experiences with WtE technologies and assess their potential applicability in Iraq. The study explores various WtE methods, including incineration, gasification, anaerobic digestion, and landfill gas recovery, emphasizing their environmental and economic benefits. Drawing from case studies in China, Germany, Sweden, and Japan, the research highlights key elements of success such as supportive legal frameworks, balanced risk-sharing mechanisms, and active community involvement. In contrast, Iraq faces several obstacles, including inconsistent waste composition, regulatory gaps, and limited financial capacity. The findings suggest that the successful adoption of WtE technologies in Iraq requires integrated policy reforms, sustainable financing strategies, institutional strengthening, and effective public-private partnerships. These measures are essential to ensure that WtE becomes a practical and sustainable component of Iraq’s future waste and energy management strategies.